Enhancing cancer care through a knowledge-sharing model: a systematic review of Project ECHO® programmes in India - Sangeeta Bhuyan; Shikha Yadav; Amit Verma; Shama Bhati; Ankit Anand; Sandeep Bhalla; Apoorva Karan Rai (BMC Cancer)
Abstract Background Cancer poses a life-threatening public health challenge, particularly impacting low- and middle-income countries (LMICs). This study focuses on India, where the cancer burden is substantial, with approximately 1.2 million new cancer cases recorded in 2020, emphasising the urgent need for effective prevention, early detection, treatment, and support services. The lack of local workforce capacity in rural areas exacerbates this challenge, necessitating collaborative efforts. The nonprofit organization Extension for Community Healthcare Outcomes (ECHO) employs the ‘Hub and Spoke’ model in India to bridge gaps in cancer care. The review aimed to assess the scale and impact of ECHO’s initiatives, evaluate findings, examine the model’s implementation, and assess its acceptability among healthcare professionals (HCPs) in preventing and treating cancer. Method This systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Eight studies, comprising six quasi-experimental and two observational studies, employing the ECHO Model for cancer care training programmes were identified. The quality of the selected articles was assessed using a standardized critical appraisal tool developed by the Joanna Briggs Institute (JBI). Results The findings reveal that ECHO India actively collaborates with experts and institutions, conducting programmes and webinars in 12 states/Union Territories to enhance professionals’ expertise in cancer care. Published literature, though limited, emphasises ECHO’s training impact, with knowledge gains ranging from 7% to 51%. The model’s adoption, retention, and reach are evident through 24 institutes/hubs implementing ECHO programmes in oncology. However, challenges such as low pre post assessment response rate and internet connectivity were observed. Conclusion ECHO India’s work in cancer care is substantial, addressing gaps in workforce capacity. The systematic review highlights the need for more publications to capture ECHO’s impact comprehensively. The findings contribute valuable insights to ongoing efforts to reduce India’s cancer burden and improve the well-being of its population.